Case Report: A FBN1 frameshift-and-nonsense mutation and aortic dissection in Marfan syndrome - Su, Chao; Zeng, Linjun; Lu, Haocheng; Wang, Zanxin; Wei, Minxin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMarfan syndrome (MFS) is an autosomal dominant connective tissue disorder primarily affecting the cardiovascular, ocular, and skeletal systems. Cardiovascular complications are the leading cause of mortality in MFS. Mutations in the FBN1 gene, which encodes fibrillin-1, a critical extracellular matrix protein, are the predominant cause of the disorder.Case presentationOn March 11, 2024, we diagnosed a 30-year-old female proband with MFS based on the revised Ghent criteria, presenting with aortic root aneurysm, aortic dissection, multiple skeletal abnormalities, and a family history of MFS. Whole-exome sequencing followed by Sanger sequencing confirmation identified a novel inherited insertion mutation (c.4991dupA) in exon 40 of the FBN1 gene. We performed valve-sparing aortic root replacement (David Procedure) and total aortic arch replacement using a tetrafurcated graft, along with the implantation of a specially designed frozen elephant trunk in the descending aorta (Sun's Procedure). Postoperatively, the patient underwent biweekly clinical follow-ups for three months. No treatment-related adverse events were reported during the monitoring period.ConclusionThe diagnosis of MFS requires an integrated approach, combining clinical manifestations, imaging studies, and genetic analysis. This novel mutation is associated with severe skeletal manifestations and life-threatening cardiovascular abnormalities, underscoring its clinical relevance. Its association with aggressive phenotypes enhances genotype-phenotype correlations. Importantly, these findings highlight the imperative need for early intervention in high-risk individuals by bridging genetic discovery to clinical practice.